Гепатопротекторное и антидисбиотическое действие высокоолеинового подсолнечного масла (экспериментальное исследование) = Hepatoprotective and antidysbiotic effects of high oleic sunflower oil (experimental investigation) - Ye. M. Levchenko (Kazimierz Wielki University, 2015)
Levchenko Ye. M. Гепатопротекторное и антидисбиотическое действие высокоолеинового подсолнечного масла (экспериментальное исследование) = Hepatoprotective and antidysbiotic effects of high oleic sunflower oil (experimental investigation). Journal of Education, Health and Sport. 2015;5(11):735-744. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.48417 http://ojs.ukw.edu.pl/index.php/johs/article/view/3436 http://pbn.nauka.gov.pl/works/722454   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   УДК 616.33:342.092   ГЕПАТОПРОТЕКТОРНОЕ И АНТИДИСБИОТИЧЕСКОЕ ДЕЙСТВИЕ ВЫСОКООЛЕИНОВОГО ПОДСОЛНЕЧНОГО МАСЛА (ЭКСПЕРИМЕНТАЛЬНОЕ ИССЛЕДОВАНИЕ)   Е. М. Левченко   Коммунальное учреждение «Одесская областная клиническая больница МЗУ»,  г. Одесса, Украина e-mail: flavan@mail.ru   Резюме Обычное подсолнечное масло (высоколинолевое) вызывает у крыс развитие стеатоза печени. Высокоолеиновое подсолнечное масло оказывает гепатопротекторное и антидисбиотическое действие.   Ключевые слова: подсолнечное масло, олеиновая кислота, печень, дисбиоз, жировой обмен.   HEPATOPROTECTIVE AND ANTIDYSBIOTIC EFFECTS OF HIGH OLEIC SUNFLOWER OIL (EXPERIMENTAL INVESTIGATION)   Ye. M. Levchenko   Municipal Institution «Odessa Regional Hospital», Odessa, Ukraine e-mail: flavan@mail.ru   Summary Aim: To make comparative estimate of action on liver by high oleic sunflower oil. Methods: Usual (linoleic) sunflower oil and high oleic sunflower oil were used. Rats were feed nonfat ration (NFR) - 1 group, NFR + 5 % usual sunflower oil - 2 group, and NFR + 5 % high oleic sunflower oil - 3 group. The feeding was continued 30 days. The content of triglycerides (TG), common cholesterine (CC) malondialdegyde (MDA), activities of elastase, urease, lysozyme, catalase, alkaline phosphatase (AP) were determined in the homogenates of liver. Activities of  AP and ALT were determined in serum. The degree of dysbiosis was calculated by using the ratio of relative activities of urease and lysozyme. Antioxydante-prooxydante index API was calculated by ratio of catalase activity and content of MDA. Results: The increase of TG and CC contents and the activities of elastase and AP was stated in liver. High oleic sunflower oil no rised the levels of TG, CC, elastase and AP but decreased the levels of urease activity and dysbiosis degree in liver. Conclusion: The high oleic sunflower oil exerts hepatoprotective and antidysbiotic actions in contrast to linoleic sunflower oil.   Keywords: sunflower oil, oleic acid, liver, dysbiosis, fatty metabolism.